Analysis of the Influence of Economic Growth, Investment, and Unemployment Rate on Inequality between Regions in West Nusa Tenggara - Siti Rahmawati; Iwan Harsono; Muaidy Yasin (Indonesian Development Economics and Localities, 2025)
This study aims to analyze how economic growth, investment and unemployment rates affect inequality between regions in NTB. This study is a quantitative study. In this study, data collection was carried out directly through the Central Statistics Agency (BPS) of NTB Province. The data analysis method used in this study is panel data regression analysis using eviews 12. The results of this study indicate that economic growth and investment have a positive and significant effect on inequality between regions in NTB, while the unemployment rate has a negative and insignificant effect on inequality, simultaneously the variables of economic growth, investment and unemployment rates have a significant effect on inequality between regions in NTB.